Efficacy of early Mycoplasma hyopneumoniae vaccination against mixed respiratory disease in older fattening pigs. (22nd February 2014) - Del Pozo Sacristán, R.; Sierens, A.; Marchioro, S. B.; Vangroenweghe, F.; Jourquin, J.; Labarque, G.; Haesebrouck, F.; Maes, D.
Abstract : The present field study investigated the efficacy of early Mycoplasma hyopneumoniae vaccination in a farrow‐to‐finish pig herd with respiratory disease late in the fattening period due to combined infections with M hyopneumoniae and viral pathogens. Five hundred and forty piglets were randomly divided into three groups of 180 piglets each: two groups were vaccinated (Stellamune Once) at either 7 (V1) or 21 days of age (V2), and a third group was left non‐vaccinated (NV). The three treatment groups were housed in different pens within the same compartment during the nursery period, and were housed in different but identical compartments during the fattening period. The efficacy was evaluated using performance and pneumonia lesions. The average daily weight gain during the fattening period was 19 (V1) and 18 g/day (V2) higher in both vaccinated groups when compared with the NV group. However, the difference was not statistically significant (P>0.05). The prevalence of pneumonia was significantly lower in both vaccinated groups (V1: 71.5 and V2: 67.1 per cent) when compared with the NV group (80.2 per cent) (P<0.05). There were no significant differences between the two vaccination groups. In conclusion, in the present herd with respiratory disease during the second half of the fattening period caused by M hyopneumoniae and viral infections, prevalence of pneumonia lesions were significantly reduced and growth losses numerically (not statistically significant) decreased by both vaccination schedules.